A new species of Dolichopus (Diptera: Dolichopodidae) from Sakhalin and designation of lectotype of Dolichopus grunini Smirnov, 1948 - O.P. Negrobov (Кавказский энтомологический бюллетень, 2012)
A new species Dolichopus vadimi Negrobov, Selivanova et Maslova sp. n. is described from Sakhalin. The type specimens of Dolichopus grunini Smirnov, 1948 were examined and the lectotype is designated. The hypopygium of D. grunini is illustrated for the first time.